"By Provocative Means": Power, Protection, and Reproduction in Prince Henry's Prayer Roll. (2nd October 2017) - Gayk, Shannon
Abstract: Sometime after 1485, Prince Henry of Wales, the future Henry VIII, acquired a prayer roll containing heraldry, monograms of the holy name, thirteen miniatures, biblical incipits, and prayers, verses, and indulgences in Latin and English. This essay reads this roll as a paradigmatic artifact of fifteenth-century devotional provocation, exploring how it, like other contemporary prayer rolls, is used both to facilitate meditation on exemplars of redemptive suffering and supplication and to provide remedies for and protection against the supplicant's own suffering. The roll does so by repeatedly foregrounding the potency of mimesis, likeness, and formal reproducibility, requiring that its users believe that the power of the original can also inhere in its copies and especially when those copies also reproduce the measure or form of the original.